Understanding intentions to donate to Islamic charities online: A systematic review of theories, methods, and determinants - Rakhmawati, Rakhmawati (Journal of Islamic Economics Lariba, 2025)
IntroductionThe rapid development of digital technology has transformed Islamic philanthropic practices by enabling zakat, waqf, infaq, and sadaqah to be delivered through online platforms, mobile applications, and financial technology systems. This transformation has expanded access and efficiency while introducing new behavioral, technological, and institutional dynamics that shape how Muslims engage in charitable giving. As online Islamic donations increasingly contribute to broader agendas of Islamic social finance and sustainable development, understanding the determinants of donors’ intentions in digital environments has become an important area of scholarly inquiry. However, existing studies remain fragmented, vary in theoretical and methodological approaches, and lack an integrated synthesis focused specifically on Islamic online donation intentions.ObjectivesThis study aims to systematically review and synthesize the academic literature on intentions to donate to Islamic charities through online channels. It seeks to map the current state of research, identify dominant themes and theoretical frameworks, examine methodological trends, highlight key determinants of donation intention, and reveal gaps related to underexplored factors, contexts, and populations.MethodThe study employs a systematic literature review using a structured and transparent approach based on the PSALSAR framework. Peer-reviewed journal articles were identified through comprehensive searches of Scopus and Web of Science databases using predefined keywords related to intention, online contexts, and Islamic donation instruments. A rigorous screening and appraisal process resulted in a final sample of 23 eligible studies, which were analyzed and synthesized to extract patterns in theories, methods, variables, and empirical findings.ResultsThe review shows that research on Islamic online donation intention is dominated by quantitative studies using Structural Equation Modeling and Partial Least Squares Structural Equation Modeling. The Unified Theory of Acceptance and Use of Technology, the Technology Acceptance Model, and the Theory of Planned Behavior are the most frequently applied frameworks. Trust, religiosity, and technology acceptance consistently emerge as central determinants of online Islamic donation intention, particularly in studies on zakat and cash waqf. The literature also reveals a strong geographic concentration in a limited number of countries.ImplicationsThe findings underscore the importance of trust-building, religious motivation, and user-friendly digital systems for enhancing online Islamic donations. They also point to the need for broader theoretical perspectives, diversified methods, and expanded geographic coverage.Originality/NoveltyThis study contributes by offering a focused and comprehensive synthesis of research on Islamic online donation intentions, strengthening cumulative knowledge and providing a clear agenda for future research in digital Islamic philanthropy.